2021
DOI: 10.7759/cureus.18619
|View full text |Cite
|
Sign up to set email alerts
|

Sacroiliac Joint and Pelvic Dysfunction Due to Symphysiolysis in Postpartum Women

Abstract: Pregnancy-related pain in the sacroiliac joint (SIJ), lumbosacral region, pubic symphysis, or in any combination of these joints has been coined as pelvic girdle pain (PGP) and has been estimated to affect almost half of all pregnant women. SIJ dysfunction in pregnancy is due to multiple biomechanical mechanisms, such as increased weight, change in posture, increased abdominal and intrauterine pressure, and laxity of the spine and pelvic structures. Moreover, when compared to men, women have increased SIJ mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
1
11
0
4
Order By: Relevance
“…In this line the present study showed that females had significantly higher odds for pain in the hip. This has been observed previously [38] and has been linked to specific changes causing laxity in spine and pelvic structures [64]. Sex discrepancies have been observed for shoulder pain [39] and the present study observed a similar directional pattern although not statistically significant.…”
Section: Individual Risk Factorssupporting
confidence: 84%
“…In this line the present study showed that females had significantly higher odds for pain in the hip. This has been observed previously [38] and has been linked to specific changes causing laxity in spine and pelvic structures [64]. Sex discrepancies have been observed for shoulder pain [39] and the present study observed a similar directional pattern although not statistically significant.…”
Section: Individual Risk Factorssupporting
confidence: 84%
“…It is shown that leg length discrepancies greater than 2 cm can contribute to long-term pathology and lower back pain [8], however, in this case, the leg length discrepancy showed to be more of a marker of her sacropelvic dysfunction. Sacroiliac joint disorders affect the entire sacropelvic girdle, which can subsequently lead to short let syndrome [9]. Because lower back pain is so common, there are a variety of treatment options, such as physical therapy, stabilization belts, acupuncture, massage, nerve stimulation, muscle relaxants, pain relievers, relaxation, and yoga [7].…”
Section: Discussionmentioning
confidence: 99%
“…Although SIJ pain and dysfunction are characteristically linked to osteoarthritic degeneration, postpartum pelvic girdle pain has recently been appreciated as an antecedent to chronic SIJ problems. 27 It has been estimated that almost 10% of women continue to have chronically severe pelvic pain of SIJ origin two years postpartum. 27 A number of studies suggest that minimally invasive SIJ fusion is effective in attenuating the impact of pelvic pain on function and quality of life in these patients.…”
Section: Biomechanical and Clinical Correlatesmentioning
confidence: 99%
“… 27 It has been estimated that almost 10% of women continue to have chronically severe pelvic pain of SIJ origin two years postpartum. 27 A number of studies suggest that minimally invasive SIJ fusion is effective in attenuating the impact of pelvic pain on function and quality of life in these patients. 27 , 28 Ongoing research in this key area is being undertaken to optimize clinical outcomes using a patient-tailored approach in selecting the appropriate surgical option for this important sub-population.…”
Section: Biomechanical and Clinical Correlatesmentioning
confidence: 99%